Sacral Osteomyelitis After Robotic Sacrocolpopexy. Issue 1 (January 2016) - Feng, Tom S.; Thum, Dennis J.; Anger, Jennifer T.; Eilber, Karyn S.
Abstract : Background: Robotic-assisted abdominal sacrocolpopexy (RASC) is an effective procedure for the surgical treatment of vaginal vault prolapse associated with a rare, but serious, risk of sacral osteomyelitis. Case: We report a case of Bacteroides fragilis sacral osteomyelitis after RASC that presented only as back pain. Treatment included intravenous antibiotics and abdominal exploration with removal of sacral mesh. Conclusions: Sacral osteomyelitis is a rare complication following RASC and may present only as back pain without constitutional symptoms. Intravenous antibiotics and surgical excision of sacral mesh are routinely performed, but preservation of vaginal mesh is a viable option. The clinician should have a high index of suspicion for osteomyelitis in any patient who presents with back pain after RASC, regardless of absence of other presenting symptoms. Abstract : We report a case of sacral osteomyelitis after robotic-assisted abdominal sacrocolpopexy that required intravenous antibiotics as well as removal of infected mesh.